2013
DOI: 10.1007/s11230-013-9439-2
|View full text |Cite
|
Sign up to set email alerts
|

Hirudinella ventricosa (Pallas, 1774) Baird, 1853 represents a species complex based on ribosomal DNA

Abstract: Digeneans in the genus Hirudinella de Blainville, 1828 (Hirudinellidae) from three species of pelagic fishes, Acanthocybium solandri (Cuvier), Makaira nigricans Lacépède and Thunnus albacares (Bonnaterre), and one benthic fish, Mulloidichthys martinicus (Cuvier), from the Gulf of Mexico are investigated using comparison of ribosomal DNA. Four species are identified based on molecular differences: Hirudinella ventricosa (Pallas, 1774) Baird, 1853 from A. solandri, Hirudinella ahi Yamaguti, 1970 from T. albacare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Before the present study, GenBank held sequence data for 3 markers ( [43]. As additional studies incorporate and publish azygiid molecular sequence data, a better understanding of interrelationships of azygiid genera will likely emerge; however, at present, impactful phylogenetics is out of reach, simply for lack of available sequence data.…”
Section: Molecular Datamentioning
confidence: 98%
See 2 more Smart Citations
“…Before the present study, GenBank held sequence data for 3 markers ( [43]. As additional studies incorporate and publish azygiid molecular sequence data, a better understanding of interrelationships of azygiid genera will likely emerge; however, at present, impactful phylogenetics is out of reach, simply for lack of available sequence data.…”
Section: Molecular Datamentioning
confidence: 98%
“…Including the present study, molecular sequence data exist only for Proterometra sp. [43] and P. epholkos, despite marked advances in molecular systematics of trematodes [76]. Sequence data for the commonly applied markers (ITS2, 18S, 28S) can help throw light on the identity of species that have been reported in the literature.…”
Section: Molecular Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Jousson et al, 2000;Hunter et al, 2010;Calhoun et al, 2013;Curran et al, 2013). Especially where the species occur in sympatry, we suspect that circumstances comparable to those discussed above have underpinned trematode speciation.…”
Section: Genus Level Host-specificitymentioning
confidence: 86%
“…Calhoun et al (2013) identifi ed four species of Hirudinella (H. ventricosa, H. ahi and two unidentifi ed species) from Gulf of Mexico on the basis of 3' end of 18S, ITS-1, 5.8S, ITS-2 and 5' end of 28S (D1-D3 domain) region sequences. Through analyses of especially ITS region, it was observed that Hirudinella is not the monotypic genus.…”
Section: Hirudinellidae (Dollfus 1932)mentioning
confidence: 99%